A Ghd7‐centered regulatory network provides a mechanistic approximation to optimal heterosis in an elite rice hybrid. (25th August 2022) - Wang, Xianmeng; Zhou, Tianhao; Li, Guangwei; Yao, Wen; Hu, Wei; Wei, Xin; Che, Jian; Yang, Haichuan; Shao, Lin; Hua, Jinping; Li, Xianghua; Xiao, Jinghua; et al.
SUMMARY: Heterosis refers to the superior performance of hybrids over their parents, which is a general phenomenon occurring in diverse organisms. Many commercial hybrids produce high yield without delayed flowering, which we refer to as optimal heterosis and is desired in hybrid breeding. Here, we attempted to illustrate the genomic basis of optimal heterosis by reinvestigating the single‐locus quantitative trait loci and digenic interactions of two traits, the number of spikelets per panicle (SP) and heading date (HD), using recombinant inbred lines and 'immortalized F2 s' derived from the elite rice ( Oryza sativa ) hybrid Shanyou 63. Our analysis revealed a regulatory network that may provide an approximation to the genetic constitution of the optimal heterosis observed in this hybrid. In this network, Ghd7 works as the core element, and three other genes, Ghd7.1, Hd1, and Hd3a/RFT1, also have major roles. The effects of positive dominance by Ghd7 and Ghd7.1 and negative dominance by Hd1 and Hd3a/RFT1 in the hybrid background contribute the major part to the high SP without delaying HD; numerous epistatic interactions, most of which involve Ghd7, also play important roles collectively. The results expand our understanding of the genic interaction networks underlying hybrid rice breeding programs, which may be very useful in future crop genetic improvement. Significance Statement: Strong heterosis in the number of spikelets per panicle without delaying flowering is one of the most attractive features of commercial hybrids that is highly desired in breeding. A Ghd7 ‐centered regulatory network involving Ghd7.1, Hd1, Hd3a/RFT1, and a large number of other loci explains such optimal heterosis, and negative dominance (rather than positive dominance) effects of Hd1 and Hd3a/RFT1 on heading date in complex interactions in the network resulted in optimal heterosis in the hybrid.